Apparent Life-Threatening Event following Maternal Use of Temazepam during Labour - L. Damen; D. H. Visser; S. D. Sie; M. M. van Weissenbruch (Hindawi Limited, 2014)
Benzodiazepines are one of the most frequently prescribed psychotropic drugs during pregnancy. Despite the fact that these drugs have been in use for a long time, there is still debate about the safety for the developing fetus and neonate. We present a case of a newborn with an apparent life-threatening event shortly after birth following maternal temazepam use during labour and advise to be reserved in prescribing any dose of any kind of benzodiazepine during labour.